High-purity superfine electronic-grade silicon dioxide microsphere as well as preparation method and application thereof
By using ammonia water to catalyze the reaction of resorcinol, formaldehyde and tetraethyl silicate in a surfactant-free system, high-purity ultrafine electron-grade silica microspheres are formed and burned, which solves the difficulty in preparing high-purity ultrafine in the prior art. The problem of silica microspheres has achieved efficient and simple preparation technology and good application effects.
Patent Information
- Application Number
- CN202311082452.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
AI Technical Summary
It is difficult to prepare high-purity ultrafine silica microspheres that meet electronic grade requirements in the prior art, and the existing process operations are complex and difficult to industrialize.
In a surfactant-free system, ammonia water is used as a catalyst, resorcinol, formaldehyde and tetraethyl silicate react in an aqueous alcohol solution to form primary microspheres, and high-purity ultrafine electron-grade silica microspheres are obtained by burning. ball. The microsphere has a bonding structure between a mesoporous shell and a microporous inner shell.
The preparation of high-purity ultrafine silica microspheres has high preparation efficiency and simple process flow. The mesoporous shell is conducive to substance adsorption, and the microporous shell is conducive to substance storage and sustained release. It is suitable for electronics, batteries and drug operation. and other fields.
Smart Images

Figure CN119503816A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon materials, and in particular to high-purity ultrafine electronic-grade silicon dioxide microspheres and a preparation method and application thereof. Background Art
[0002] Silicon dioxide (SiO2) is a non-toxic, odorless, non-polluting inorganic material with a three-dimensional molecular network structure and many hydroxyl groups in different states on the surface. It has excellent dielectric properties, low thermal expansion coefficient, high thermal conductivity, etc. Its excellent physical properties, extremely high chemical stability and unique optical properties determine its special status in the fields of aviation, aerospace, electronic information, etc. It has become the most basic, important and critical raw material in many high-tech fields.
[0003] With the development of high-tech fields such as the electronics industry, batteries and energy storage, integrated circuits, and optical fiber communications, the demand for ultrafine silicon dioxide is increasing, and higher requirements are placed on the content of impurities in it. A lot of research has also been conducted at home and abroad on the development of high-purity ultrafine silicon dioxide. The current research directions and related intellectual property rights are mainly concentrated in the following aspects:
[0004] First, high-quality high-purity quartz ore is used as raw material, and high-purity or ultra-fine silicon dioxide is obtained through processes such as pickling, purification, complexation, calcination or grinding, such as patents CN201710367309.8, CN201610604327.9 and CN201710367309.8;
[0005] The second is the gas phase method for preparing silicon dioxide, such as CN201711123068.9 (chlorosilane vaporization combustion method), CN201811213512.0 (organic silicon slurry and siloxane mixed combustion method) and CN201880005781.X (monochlorosilane or monosilane combustion method).
[0006] The third is hydrated silica based on the precipitation method. For example, Zang Jian et al. developed a method of removing metal ions with lime at high temperature and high pressure, but this method is difficult to operate and has high operating risks; Wang Shengjin et al. used iron removal agents to reduce the insoluble trivalent iron ions to more soluble divalent iron ions, and complexed with EDTA to remove iron, but this method is difficult to remove other metal ions, and the fineness of the product cannot meet the requirements. In addition, the team members of the Supergravity Engineering Research Center of Beijing University of Chemical Technology also studied the process of preparing nano-silicon dioxide by supergravity, but it is also difficult to industrialize production at present.
[0007] The fourth is the sol-gel method. For example, patent CN201610329438.3 reports a method for preparing monodisperse silica microspheres. However, the microspheres prepared by this method have a single structure and a relatively large particle size. Patent CN201611114914.6 dissolves terminal siloxane polyether in an ethanol solution of ammonia water, then adds orthosilicate and stirs evenly, and uses a hydrothermal method to react at 100 to 120°C to obtain a monodisperse submicron silica microsphere dispersion. The dispersion is sintered at 650 to 700°C under the protection of an inert atmosphere to obtain the monodisperse submicron silica microspheres. The microspheres have a single pore structure and a particle size of micrometers.
[0008] The silica microspheres prepared by other existing patents have relatively simple pore structures and morphological structures, and the particle size is relatively large, which is difficult to meet the requirements of electronic grade. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide high-purity ultrafine electronic-grade silica microspheres that meet electronic-grade requirements, and further provide a preparation method and application of the aforementioned silica microspheres.
[0010] In order to solve the above technical problems, the present invention provides a method for preparing high-purity ultrafine electronic grade silica microspheres. In a surfactant-free system, ammonia water is used as a catalyst, and resorcinol, formaldehyde and tetraethyl silicate are reacted in an alcohol-containing aqueous solution at 45-80° C. for 5-60 minutes to obtain primary microspheres; the primary microspheres are burned in air to obtain high-purity ultrafine electronic grade silica microspheres.
[0011] Further provided are high-purity ultrafine electronic grade silica microspheres prepared by the above-mentioned preparation method.
[0012] Further provided is the use of the aforementioned silica microspheres in the preparation of electronic packaging, integrated circuits, copper-clad laminates, battery separators, electrolytes, electrode materials, molding compounds, adsorption materials, drug transporters or catalysts.
[0013] The beneficial effects of the present invention are as follows: the present invention can prepare high-purity ultrafine silica with shell-core mesoporous / microporous combination under the condition of no surfactant, the preparation efficiency is high, the process flow and operation are simple, the mesoporous outer shell is conducive to the adsorption and entry of substances, the microporous inner shell is conducive to the storage and sustained release of substances, and the flow rate of substances is controlled. The prepared silica has good application effects in the fields of electronic appliances, batteries, drug operation, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a TEM photo of the silica microspheres prepared in Example 1 of the present invention;
[0015] Figure 2This is a TEM photo of the silica microspheres prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0016] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.
[0017] The invention discloses a method for preparing high-purity ultrafine electronic grade silica microspheres. In a surfactant-free system, ammonia water is used as a catalyst, and resorcinol, formaldehyde and tetraethyl silicate are reacted in an alcohol-containing aqueous solution at 45-80° C. for 5-60 minutes to obtain primary microspheres; the primary microspheres are burned in air to obtain high-purity ultrafine electronic grade silica microspheres; wherein the high-purity ultrafine electronic grade silica microspheres include an inner layer with a microporous structure and an outer layer with a mesoporous structure.
[0018] In this embodiment, the reaction temperature is increased to 45-80°C to accelerate the balling rate, and the time difference between the hydrolysis / condensation of resorcinol and TEOS (tetraethyl silicate) and the precipitation of microparticles is reduced to reduce the time proportion of TEOS homogeneous nucleation, thereby promoting the co-assembly of TEOS hydrolysis condensation products and resorcinol / formaldehyde condensation products, that is, forming silica-coated phenolic resin / silicon dioxide core-shell microspheres (that is, the aforementioned primary microspheres), and further calcination treatment is performed to form high-purity ultrafine electronic grade silica microspheres. That is, in this embodiment, since the phenolic resin is a condensation product of resorcinol and formaldehyde, it is co-assembled with silica (TEOS hydrolysis condensation product) on the core silica formed by the TEOS homogeneous phase, so the phenolic resin is removed in the subsequent calcination process to form the mesoporous structure of the outer layer, that is, the phenolic resin is a pore-forming agent for the formation of the outer layer mesoporous structure.
[0019] In terms of specific processes, tetraethyl silicate can be rapidly hydrolyzed to form monodisperse silica microspheres in a system of water, alcohol and ammonia, but the microspheres are mainly microporous structures, which limits their applications as electrode materials, electronic packaging, etc. Therefore, the inventors designed a method for obtaining silica microspheres with a mesoporous structure using phenolic resin as a pore-forming template in a surfactant-free system. However, since the hydrolysis and condensation rate of tetraethyl silicate is generally significantly greater than the condensation rate of resorcinol-formaldehyde, if tetraethyl silicate, resorcinol and formaldehyde are added together to the aforementioned water, alcohol and ammonia system, tetraethyl silicate will be rapidly hydrolyzed and condensed to form silica microspheres. When resorcinol and formaldehyde are condensed to a sufficient amount of phenolic resin particles precipitated, the tetraethyl silicate in the system has basically reacted to form silica microspheres, and the phenolic resin particles can only be coated on the surface of silica alone to form phenolic resin-coated silica microspheres. After subsequent burning to remove the phenolic resin on the surface, only solid microporous silica microspheres can be obtained, and it is difficult to obtain silica microspheres with a core-shell structure having a composite of a mesoporous structure and a microporous structure. Therefore, in one embodiment, resorcinol, formaldehyde and tetraethyl silicate can be added sequentially to control the hydrolysis and condensation of tetraethyl silicate to produce an inner core and an outer layer of silica, and the timing of the formation of the condensation product of resorcinol and formaldehyde can be controlled to achieve co-assembly of the outer layer of silica and the resorcinol-formaldehyde condensation product and deposition on the inner core.
[0020] At the same time, the study also found that by increasing the reaction temperature, not only can the ball-forming speed be accelerated to achieve rapid preparation, but it is also found that the condensation process of resorcinol and formaldehyde is very sensitive to temperature. When the reaction temperature increases, the difference between the hydrolysis condensation rate of tetraethyl silicate and the condensation rate of resorcinol-formaldehyde will gradually decrease, which will lead to an increase in the concentration of tetraethyl silicate and its soluble condensation products in the later stage of the system. Therefore, the silica produced by homogeneous nucleation of TEOS in the early stage serves as the core. When the phenolic resin formed by the condensation of resorcinol-formaldehyde is deposited on the surface of the core, the hydrolysis condensation products of the remaining TEOS in the system are in NH4 + Under the action of, through the heterogeneous nucleation mechanism, the condensation product of resorcinol-formaldehyde is co-assembled and coated on the surface of the aforementioned core, that is, a core-shell structure is formed, and after the subsequent burning process, the phenolic resin template is removed, a mesoporous structure is formed in the outer layer of the silica microsphere, and its inner layer (i.e., the aforementioned core) forms a microporous structure. On this basis, it can be seen that the key factor for obtaining the desired high-purity ultrafine electronic grade silica microspheres is that the reaction temperature is increased to 45-80°C. At the same time, since the raw materials do not contain or contain trace amounts of metal ions, the metal content of the prepared silica microspheres is low, which can effectively meet the requirements of the electronic grade.
[0021] It should be noted that in this application, micropores and mesopores are generally defined in the art, that is, the pore structure with a pore size less than 2 nm formed on the silica microspheres is called a micropore structure, and the pore structure with a pore size between 2 and 50 nm is called a mesopore structure (or mesopore structure).
[0022] In a preferred embodiment, the preparation method comprises the following steps:
[0023] S1. Add resorcinol to an alcohol-containing aqueous solution, add aqueous ammonia, and stir evenly to obtain solution A;
[0024] S2, adding formaldehyde and tetraethyl silicate to the solution A, reacting at a reaction temperature of 45 to 80° C. for 5 to 60 minutes to obtain a turbid liquid;
[0025] S3, separating the turbid liquid, and drying the precipitate to obtain primary microspheres (silicon dioxide coated silicon dioxide / phenolic resin microspheres);
[0026] S4, carbonizing the primary microspheres to obtain high-purity ultrafine electronic grade silica microspheres.
[0027] In an optional embodiment, the calcination is carried out in air at a temperature of 600 to 1200° C. for 1 to 6 hours.
[0028] In one embodiment, the alcohol is selected from at least one of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, hemptanol, ethylene glycol, glycerol, propylene glycol, and pentaerythritol, preferably ethanol. The volume ratio of water to alcohol is 1: (2-10), preferably 1: (5-8).
[0029] In one embodiment, the formaldehyde is selected from paraformaldehyde or formaldehyde aqueous solution, preferably formaldehyde aqueous solution, and the molar ratio of formaldehyde to resorcinol is (1.5-2):1. In this embodiment, the formaldehyde and resorcinol are used as condensation raw materials of phenolic resin, so as to form a mesoporous structure in the outer layer of the silica microspheres during the burning process by using the phenolic resin as a pore-forming template. In order to form a stable cross-linked structure, it is preferred to control the molar ratio of aldehyde to phenol>1, that is, the final concentration of resorcinol in the alcohol-containing aqueous solution (the concentration of the aforementioned solution A) is preferably 2-100 mg / mL. In this embodiment, since the condensation process of resorcinol and formaldehyde is very sensitive to temperature, the reaction temperature of resorcinol and formaldehyde can be significantly accelerated by increasing the reaction temperature to ensure that when the condensation product of resorcinol-formaldehyde is precipitated, the reaction system still contains enough remaining TEOS and its soluble condensate or monomer, so as to achieve the co-assembly of phenolic resin and silica particles and co-deposition on the surface of the aforementioned core.
[0030] In one embodiment, the molar ratio of tetraethyl silicate to resorcinol is (0.5-20):1, that is, by controlling the molar ratio of the two, tetraethyl silicate can be quickly hydrolyzed to form a silica core at a reaction temperature of 45-80°C, and resorcinol and formaldehyde can condense to form a phenolic resin, and the phenolic resin can be co-assembled with the condensation product of tetraethyl silicate remaining in the system, silica, and other soluble condensation products and coated on the surface of the aforementioned silica core to form a core-shell microsphere structure of silica / phenolic resin coated silica, and in the subsequent burning process, the outer layer of the phenolic resin will be removed to form high-purity ultrafine electronic grade silica microspheres.
[0031] In one embodiment, the molar ratio of ammonia water to resorcinol is (2-20): 1. In this embodiment, the ammonia water not only acts as a catalyst, but also serves to reduce the surface polarity of the silica monomer, so as to achieve the process of co-assembly and co-coating of the silica monomer and the phenolic resin in the silica core to form a core-shell structure.
[0032] A high-purity ultrafine electronic grade silica microsphere prepared by the above-mentioned preparation method, characterized in that the particle size of the silica microsphere is ≤1000nm, and the metal ion content of the silica microsphere is ≤100ppm, that is, the prepared silica microsphere has the characteristics of high purity and ultrafineness, wherein the lower metal ion content can significantly reduce the corrosion of the silica microsphere to the device, improve the safety and life of the device, and the lower particle size can effectively improve its distribution uniformity in the material, improve the mechanical properties and electrochemical properties.
[0033] The aforementioned silica microspheres are used in the preparation of electronic packaging, integrated circuits, copper-clad laminates, battery separators, electrolytes, electrode materials, molding compounds, adsorbent materials, drug transporters or catalysts. Among them, since the silica microspheres prepared by the present invention have both microporous structures and mesoporous structures, when they are used as drug transporters / adsorbent materials, their mesoporous structures are conducive to the adsorption and entry of substances, while their microporous structures are conducive to the storage and sustained release of substances, which can realize the control of the flow rate and release rate of substances, and can also be used as silicon-based negative electrode materials for the preparation of battery electrodes to increase battery capacity. Because it has a rich pore structure and a unique core-shell structure, it has application potential in many emerging fields.
[0034] Example 1
[0035] A method for preparing core-shell structured silica microspheres comprises the following steps:
[0036] S1. Add resorcinol to the water / alcohol system, add ammonia water (25%), and stir evenly;
[0037] S2, add formaldehyde and tetraethyl silicate, react at 45°C for 60 minutes to obtain a turbid solution;
[0038] S3, separating and drying the turbid liquid to obtain silica-coated silica / phenolic resin microspheres;
[0039] S4, the microspheres were calcined at 700°C in air for 4 h to obtain silica microspheres, such as Figure 1 As shown;
[0040] The volume ratio of water to alcohol is 1:7;
[0041] The molar ratio of ammonia water to resorcinol is 11:1;
[0042] The concentration of resorcinol in the solution is 5 mg / mL;
[0043] The molar ratio of formaldehyde to resorcinol is 2:1;
[0044] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1.
[0045] After testing, the obtained silica was a core-shell structure with a dense inner layer and a loose outer layer. The average size of the silica microspheres was about 135nm, the average mesopore diameter was about 8nm, and the metal ion content was 52ppm. Figure 1 It shows that the product has a spherical morphology and a core-shell structure, with a dense inner layer and a loose outer layer.
[0046] Comparative Example 1
[0047] A method for preparing core-shell structured silica microspheres comprises the following steps:
[0048] S1. Add resorcinol to the water / alcohol system, add ammonia water (25%), and stir evenly;
[0049] S2, add formaldehyde and tetraethyl silicate, react at 25°C for 24h to obtain a turbid solution;
[0050] S3, separating and drying the turbid liquid to obtain silica-coated phenolic resin microspheres;
[0051] S4, the microspheres were calcined at 700°C in air for 4 h to obtain silica microspheres, such as Figure 2 As shown;
[0052] The volume ratio of water to alcohol is 1:7;
[0053] The molar ratio of ammonia water to resorcinol is 11:1;
[0054] The concentration of resorcinol in the solution is 5 mg / mL;
[0055] The molar ratio of formaldehyde to resorcinol is 2:1;
[0056] The molar ratio of tetraethyl silicate to resorcinol is 3.4:1.
[0057] After testing, the silica microspheres are solid structures with an average size of about 166nm, the pore size is mainly micropores, and the metal ion content is 60ppm. Figure 2 It shows that the product has a spherical morphology, uniform internal and external structures, and is relatively dense, without an obvious core-shell structure.
[0058] Example 2
[0059] A method for preparing core-shell structured silica microspheres comprises the following steps:
[0060] S1. Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly;
[0061] S2, add formaldehyde and tetraethyl silicate, react at 60°C for 30 minutes to obtain a turbid solution;
[0062] S3, separating and drying the turbid liquid to obtain silica-coated silica / phenolic resin microspheres;
[0063] S4, calcining the microspheres at 700°C in air for 4 h to obtain silica microspheres;
[0064] The volume ratio of water to alcohol is 1:7;
[0065] The molar ratio of ammonia water to resorcinol is 11:1;
[0066] The concentration of resorcinol in the solution is 5 mg / mL;
[0067] The molar ratio of formaldehyde to resorcinol is 2:1;
[0068] The molar ratio of tetraethyl silicate to resorcinol is 4:1.
[0069] After testing, the average size of the silica microspheres was about 108 nm, the average mesopore diameter was about 14 nm, and the metal ion content was 53 ppm.
[0070] Example 3
[0071] A method for preparing core-shell structured silica microspheres comprises the following steps:
[0072] S1. Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly;
[0073] S2, add formaldehyde and tetraethyl silicate, react at 60°C for 60 minutes to obtain a turbid solution;
[0074] S3, separating and drying the turbid liquid to obtain silica-coated silica / phenolic resin microspheres;
[0075] S4, calcining the microspheres at 700°C in air for 4 h to obtain silica microspheres;
[0076] The volume ratio of water to alcohol is 1:7;
[0077] The molar ratio of ammonia water to resorcinol is 11:1;
[0078] The concentration of resorcinol in the solution is 5 mg / mL;
[0079] The molar ratio of formaldehyde to resorcinol is 2:1;
[0080] The molar ratio of tetraethyl silicate to resorcinol is 4:1.
[0081] After testing, the average size of the silica microspheres was about 112 nm, the average mesopore diameter was about 13 nm, and the metal ion content was 48 ppm.
[0082] Example 4
[0083] A method for preparing core-shell structured silica microspheres comprises the following steps:
[0084] S1. Add resorcinol to a water / alcohol system, add ammonia water, and stir evenly;
[0085] S2, add formaldehyde and tetraethyl silicate, react at 75°C for 30 minutes to obtain a turbid solution;
[0086] S3, separating and drying the turbid liquid to obtain silica-coated silica / phenolic resin microspheres;
[0087] S4, calcining the microspheres at 700°C in air for 4 h to obtain silica microspheres;
[0088] The volume ratio of water to alcohol is 1:7;
[0089] The molar ratio of ammonia water to resorcinol is 11:1;
[0090] The concentration of resorcinol in the solution is 5 mg / mL;
[0091] The molar ratio of formaldehyde to resorcinol is 2:1;
[0092] The molar ratio of tetraethyl silicate to resorcinol is 4:1.
[0093] After testing, the average size of the silica microspheres was about 83 nm, the average mesopore diameter was about 15 nm, and the metal ion content was 49 ppm.
[0094] In summary, the present invention can prepare high-purity ultrafine silica with shell-core mesoporous / microporous combination under the condition of no surfactant, with high preparation efficiency, simple process flow and operation, the mesoporous outer shell is conducive to the adsorption and entry of substances, the microporous inner shell is conducive to the storage and sustained release of substances, and the flow rate of substances is controlled. The prepared silica has good application effects in the fields of electronic appliances, batteries, drug operation, etc., especially can be used as a silicon-based negative electrode material for preparing battery electrodes to improve the capacity of the battery.
[0095] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing high-purity ultrafine electronic grade silica microspheres, characterized in that: In a surfactant-free system, ammonia water is used as a catalyst, and resorcinol, formaldehyde and tetraethyl silicate are reacted in an alcohol-containing aqueous solution at 45-80° C. for 5-60 minutes to obtain primary microspheres; the primary microspheres are burned in air to obtain high-purity ultrafine electronic grade silica microspheres.
2. The preparation method according to claim 1, characterized in that: The high-purity ultrafine electronic grade silica microspheres include an inner layer with a microporous structure and an outer layer with a mesoporous structure.
3. The preparation method according to claim 1, characterized in that: The alcohol is selected from at least one of methanol, ethanol, propanol, butanol, octanol, pentanol, hexanol, heptanol, heptyl alcohol, ethylene glycol, glycerol, propylene glycol and pentaerythritol.
4. The preparation method according to claim 1, characterized in that: The formaldehyde is selected from paraformaldehyde or formaldehyde aqueous solution, and the molar ratio of the formaldehyde to resorcinol is (1.5-2):
1.
5. The preparation method according to claim 1, characterized in that: In the alcohol-containing aqueous solution, the volume ratio of water to alcohol is 1:(2-10).
6. The preparation method according to claim 1, characterized in that: The final concentration of the resorcinol in the alcohol-containing aqueous solution is 2 to 100 mg / mL.
7. The preparation method according to claim 1, characterized in that: The molar ratio of the ammonia water to resorcinol is (2-20):
1.
8. The preparation method according to claim 1, characterized in that: The molar ratio of tetraethyl silicate to resorcinol is (0.5-20):
1.
9. A high-purity ultrafine electronic grade silica microsphere prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The particle size of the silica microspheres is ≤1000nm, and the metal ion content of the silica microspheres is ≤100ppm.
10. Use of the silica microspheres as claimed in claim 9 in the preparation of electronic packaging, integrated circuits, copper-clad laminates, battery separators, electrolytes, electrode materials, molding compounds, adsorption materials, drug transporters or catalysts.
Citation Information
Patent Citations
A method for preparing monodisperse silica microspheres
CN106009346B
Preparation method of electronic-grade ultrafine composite silica micropowder for integrated circuit substrate
CN106255315A
A monodisperse submicron-sized silica microsphere and its preparation method
CN106745009B
Method for preparing nano-sized spherical silicon micropowder by flame method
CN107055554A
Production process and device of nano fumed silica
CN107777693A